Maximum product spacings method for the estimation of parameters of generalized inverted exponential distribution under Progressive Type II Censoring. Issue 2 (3rd March 2016) - Kumar Singh, Rajwant; Kumar Singh, Sanjay; Singh, Umesh
Abstract: In this paper, we have discussed the problem of point estimation of the shape and scale parameters of Generalized Inverted Exponential Distribution (GIED) based on progressive type-II censored samples. The Method of product of spacings is used to estimate the parameters of the model along with reliability and hazard functions. The proposed estimators have been compared with the corresponding maximum likelihood estimators on the basis of Monte Carlo Simulation study. Finally, a real data set has been considered to illustrate the practical utility of the paper.